Relational Pluralism Within and Between Organizations - Shipilov, Andrew; Gulati, Ranjay; Kilduff, Martin; Li, Stan; Tsai, Wenpin (Academy of Management Journal, 2014)
Relational pluralism exists when actors maintain multiple kinds of relationships with one another and develop multiple identities as a result. The outcomes of relational pluralism can include greater flexibility in building network ties, more stable exchange relationships, and the ability to adopt tailored innovations. We develop a typology of relational pluralism and examine both the positive and negative features of relational pluralism inside and across organizations. We conclude with a discussion of future directions for research.